COVID-19- or Tramadol-induced Seizure: A Differential Diagnosis in Young People: COVID-19 induced seizure or tramadol - Nekoueifard, Solmaz; Majidi, Mohammad (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Coronavirus disease 2019 (COVID-19) was first declared in December 2019 from Wuhan, China [1, 2]. It then has been reported a pandemic in March 2020 by the World Health Organization [3]. Clinical features of COVID-19 are different from asymptomatic to mild to moderate symptoms, such as fever, headache, myalgia, sore throat, anosmia, cough, fatigue headache, hemoptysis, and dyspnea to the life-threatening complications, including shock, pneumonia, acute respiratory distress syndrome, myocarditis, myocardial infarction, acute kidney injury, multi-organ failure, and even death [1, 2].